Excess volume and surface tension of some flavoured binary alcohols at temperatures 298.15, 308.15 and 318.15 K. (2nd November 2019) - Awasthi, Naveen; Kumar, Atul; Srivastava, Urvashi; Srivastava, Kirti; Shukla, Rajeev K.
ABSTRACT: From the measured work of Ching-Ta and Chein-Hsiun Tu, we have presented the theoretical results of Surface tension and excess volume for three binary systems: namely 2-Propanol+Benzyl alcohol(1), 2-Propanol+2-Phenylethnol(2) and Benzyl alcohol+2-Phenylethanol(3) at temperatures 298.15, 308.15 and 318.15 K and atmospheric pressure over the concentration range 0.05–0.95. Theoretical results were computed from Flory model, Ramaswamy and Anbananthan (RA) model and model devised by Glinski, and studied the mixing properties and interactions of these liquids. Deviations in the surface tension (∆ σ ) were evaluated and fitted to the Redlich–Kister polynomial equation to derive the binary coefficients and standard errors. Moreover, McAllister multi-body interaction model based on Eyring's theory of absolute reaction rates has also been applied. For liquid mixtures, the free energy of activation is additive, based on the proportions of the different components of the mixture and interactions of like and unlike molecules. The behaviour of the liquids was studied and correlated with the molecular interactions from these liquid state models. Conclusively, these non-associated and associated models were compared and tested for different systems showing that the McAllister multi-body interaction model yields good results as compared to associated models, while Flory model shows more deviations.